PENERAPAN METODE MEMBACA DAN MENULIS AL-QUR’AN DI TPQ AL-AZHAR NAGARI ABAI SIAT - Fitri, Mariani; Iswantir, Iswantir (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
This research is motivated by the method of reading and writing the Qur'an, at TPQ Al-Azhar there are many students who like learning to read and write the Qur'an. -The Koran that is applied in the TPQ? How to apply the reading and writing method? This research uses a descriptive-qualitative approach with a field research study design (Field research). In this study, researchers used the methods of observation, interviews, and documentation as a means of collecting data from primary and secondary data sources. The results of this research are: (1) The application of the method of reading the Qur'an at TPQ Al-Azhar is the bandongan, sorogan, memorization and lecture methods, from the past until now. (2) The application of the method of writing the Qur'an at TPQ Al-Azhar is Imla' manqul, Imla'mandhur, Imla' ghairu al-mandhur, Imla' ikhtibari. (3) The supporting and inhibiting factors in TPQ Al-Azhar are factors that support the Al-Qur'an learning process, namely the teacher always gives homework in the form of writing and memorizing certain verses and then the next day it is deposited and guided with the aim of being more enthusiastic and active in learning Al-Qur'an. And the inhibiting factor is being lazy or bored during the learning process, this can happen because the teacher is monotonous or the lessons are less interesting.